2018
DOI: 10.3389/fnagi.2018.00138
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Aβ42/40 Ratio for Detection of Alzheimer Disease Pathology in Clinical Routine: The PLMR Scale

Abstract: Background: Cerebrospinal fluid (CSF) biomarkers (Aβ peptides and tau proteins) improved the diagnosis of Alzheimer’s disease (AD) in research and clinical settings. We previously described the PLM-scale (Paris-Lille-Montpellier study), which combines Aβ42, tau, and phosphorylated ptau(181) biomarkers in an easy to use and clinically relevant way. The purpose of this work is to evaluate an optimized PLMR-scale (PLM ratio scale) that now includes the Aβ42/Aβ40 ratio to detect AD versus non-AD (NAD) participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…In the present study, we showed that the Aβ 42/40 ratio changes half of previously considered “uninformative” CSF profiles into A+T+, the biological definition of AD [16] . This result is strikingly similar to the ones of previous studies [33] , [34] , [46] .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we showed that the Aβ 42/40 ratio changes half of previously considered “uninformative” CSF profiles into A+T+, the biological definition of AD [16] . This result is strikingly similar to the ones of previous studies [33] , [34] , [46] .…”
Section: Discussionsupporting
confidence: 92%
“…Another derivative of Aβ that can act as a potential AD biomarker is Aβ40, which is the most abundant isoform present in the CSF. Although there are no substantial changes in the levels of CSF Aβ40 in AD patients and the CSF concentration of Aβ40 does not correlate with amyloid deposits in the brain, a significant decrease can be seen when amyloidogenic peptide levels are compared by the CSF Aβ42/Aβ40 ratio [15][16][17][18][19][20][21][22] . This ratiometric analysis is more reliable than solely observing Aβ42 concentrations because it compensates for intraindividual fluctuations within AD patients.…”
Section: Cerebrospinal Fluidmentioning
confidence: 93%
“…Commercial ELISA CSF Aβ42 has an inverse correlation with amyloid burden, as measured by PIB-PET [10][11][12][13][14] Commercial immunoassays Ratios of CSF Aβ42 to other Aβ isoforms (Aβ40 or Aβ38) are strongly correlated with accurate AD diagnosis [15][16][17][18][19][20][21][22][23][24][25][26]…”
Section: Aβ42mentioning
confidence: 99%
See 1 more Smart Citation
“…In the cerebrospinal fluid (CSF) of AD patients, Aβ1-38 and particularly Aβ1-40 are elevated relative to healthy controls, whereas Aβ1-42 is decreased [39][40][41] . Currently, the CSF Aβ42/40 ratio is one of the most widely used diagnostic marker for mild cognitive impairment (MCI) and AD patients, and may be used to predict further cognitive decline 39,40,42,43 .…”
Section: mentioning
confidence: 99%